17β-Estradiol Induces Mitophagy Upregulation to Protect Chondrocytes via the SIRT1-Mediated AMPK/mTOR Signaling Pathway - Mei, Runhong; Lou, Peng; You, Guanchao; Jiang, Tianlong; Yu, Xuefeng; Guo, Lei (Frontiers in Endocrinology, 2021)
Increasing evidence reveals that estrogen, especially 17β-estradiol (17β-E2), is associated with articular cartilage metabolism disorder and postmenopausal osteoarthritis (OA). SIRT1, AMPK and mTOR are regarded as critical mitophagy regulators. Recent studies have shown that mitophagy displays a protective effect against OA, but the molecular mechanism is not well known. This study aimed to investigate the effect of 17β-E2 on Sirtuin-1 (SIRT1) expression and the induction of mitophagy upregulation by 17β-E2 via the SIRT1-mediated AMP-activated protein kinase (AMPK)/mammalian target of the rapamycin (mTOR) signaling pathway to protect chondrocytes. ATDC5 chondrocytes were treated with different concentrations of 17β-E2 (0 M, 1 × 10-9 M, 1 × 10-8 M, and 1 × 10-7 M) for 24 h or pretreatment with or without NAM (SIRT1 inhibitor), Compound C (AMPK inhibitor) and S1842 (mTOR inhibitor) for 30 min prior to treatment with 17β-E2 (1 × 10-7 M) for 24 in each groups. Expression of SIRT1 was evaluated by real-time PCR, Western blotting and confocal immunofluorescence staining. Then, the mitophagosomes in cells were observed under a transmission electron microscopy (TEM), and the AMPK/mTOR signaling pathway was detected by Western blotting. The mitophagy-related proteins, p-AMPK, p-mTOR, p-JNK and p-p38 were also identified by Western blot analysis. The chondrocytes viability and proliferation were determined by MTT and 5-Bromo-2’-deoxyuridine (BrdU) assay. These experiments were independently repeated three times. The study found that 17β-E2 increased the expression level of SIRT1, p-AMPK, and mitophagy-related proteins but decreased p-mTOR expression, and then induced mitophagy upregulation in chondrocytes. More mitochondrial autophagosomes were observed in 17β-E2-treated chondrocytes under a transmission electron microscope. Also, 17β-E2 improved cell viability and proliferation with the higher expression of SIRT1 and activation of the AMPK/mTOR signaling pathway. However, SIRT1 inhibitor nicotinamide (NAM) and AMPK inhibitor Compound C blocked the beneficial effect of 17β-E2. In summary, this study was novel in demonstrating that 17β-E2 induced mitophagy upregulation to protect chondrocytes via the SIRT1-mediated AMPK/mTOR signaling pathway.